An examination of the relationship between the extent of a flexible culture and the levers of control system: The key role of beliefs control. (December 2016) - Heinicke, Anja; Guenther, Thomas W.; Widener, Sally K.
Abstract: This study examines the relationship between the extent of a flexible culture and the emphasis placed on the Levers of Control (LoC) Framework. We use a structural equation model to investigate whether the extent a firm emphasizes a flexible culture is related to the emphasis placed on beliefs, boundary, diagnostic and interactive controls. We also examine whether a key contingency variable, size, moderates our proposed model. Using survey data from 267 top managers of medium-sized firms, we find, as expected, that the more firms emphasize a flexible culture, the more they emphasize the use of beliefs controls. We show that this finding is robust to firm size. Thus, we conclude that the emphasis placed on beliefs control is an important control mechanism in organizations that emphasize a flexible culture. We also conclude that size moderates the associations among the control levers. Relative to the subsample of smaller firms, in the subsample of larger firms the beliefs and boundary control uses of performance measures are more reinforcing of each other while the diagnostic use of performance measures and boundary control act more as replacements for each other.